Enhancing the Productive Performance of Broiler Chickens by Adding Spirulina platensis Compared with Probiotic, Prebiotics, and Oxytetracycline - Atiyah, Wisam R; Hamood, Mohanad F (The Iraqi Journal of Veterinary Medicine, 2021)
This study was conducted in order to find out the effect of Spirulina platensis (S. platensis) algae mixed with drinking water (2%) on the production performance of broiler chickens infected with or without Enterococcus faecalis (E. faecalis) and compare it with the effects of probiotics (containing Lactobacillus acidophilus, L. casi, L. reuteri, and Bacillus subtillis), prebiotics (containing antioxidants and a group of vitamins) as well as oxytetracycline. The experiment included 350 one day old (Ross-308) broiler chicks, randomly divided into 7 groups by 50 chicks per group for 35 days. The groups were divided as follows: T1: infected experimentally with E. faecalis only, T2: treated with S. platensis, T3: infected experimentally with E. faecalis and treated with 2% S. platensis, T4: infected experimentally with E. faecalis and treated with probiotic, T5: infected experimentally with E. faecalis and treated with prebiotic, T6: infected experimentally with E. faecalis and treated with oxytetracycline, and T7: control group without any addition. Weekly live body weight and weekly body weight gain were measured as well as weekly feed intake and feed conversion rate for broiler chickens were estimated. The current study proved that S. platensis algae added to drinking water (2%) in T2 and T3 groups had caused a significant increase (P<0.05) in the weekly live body weight and weekly body weight gain, Spirulina also caused a significant decrease (P<0.05) in weekly feed intake and feed conversion rate for broiler chickens. Therefore, S. platensis could be a suitable alternative to some feed additives such as probiotics, prebiotics, and antibiotics in addition to the ability of Spirulina to reduce the symptoms of E. faecalis.